Rare bird documentation form for Peregrine Falcon at Saylorville Reservoir, 1986 - Dinsmore, Stephen J.et al (1986)
Rare bird documentation form for a Peregrine Falcon at Saylorville Reservoir in Polk County, IA on March 20, 1986. Epson - sheet feed